1999
DOI: 10.1111/j.1749-6632.1999.tb09232.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antioxidant Trace Elements on the Response of Cardiac Tissue to Oxidative Stressa

Abstract: It is now well established that several trace elements, because of their involvement in the catalytic activity and spatial conformation of antioxidant enzymes, may contribute to the prevention of oxidative stress such as occurs upon reperfusion of ischemic tissue. The aim of this paper is (1) to review the role of these trace elements (Cu, Mn, Se, and Zn) in antioxidant cellular defenses in the course of post-ischemic reperfusion of cardiac tissue, (2) to provide experimental data suggesting that variations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 79 publications
0
26
1
2
Order By: Relevance
“…Cu, Zn, Mn, and Se were found to be important for apolipoprotein (apo), the major structural protein of lipoprotein, so as to participate in lipid metabolism [7][8][9][10][11]. Cu, Zn, Mn, and Se are also essential for catalytic activity and proper spatial conformation of antioxidant enzymes such as superoxide dismutase (SOD), catalase, and glutathione peroxidase (GSH-Px) and thereby play important roles in the antioxidant defense and lipid peroxidation [12]. In accordance with mechanism above, Se was observed to exhibit protective roles on risks of oxidative damage by lowering lipid concentrations and increasing antioxidant enzyme activities when animals were challenged with cigarette smoke and enflurane anesthetized [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Cu, Zn, Mn, and Se were found to be important for apolipoprotein (apo), the major structural protein of lipoprotein, so as to participate in lipid metabolism [7][8][9][10][11]. Cu, Zn, Mn, and Se are also essential for catalytic activity and proper spatial conformation of antioxidant enzymes such as superoxide dismutase (SOD), catalase, and glutathione peroxidase (GSH-Px) and thereby play important roles in the antioxidant defense and lipid peroxidation [12]. In accordance with mechanism above, Se was observed to exhibit protective roles on risks of oxidative damage by lowering lipid concentrations and increasing antioxidant enzyme activities when animals were challenged with cigarette smoke and enflurane anesthetized [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, vitamin C may indicate a significant role to protect the cells from the invasion of free radicals. It can be proposed that despite cellular protective action of vitamins against oxidative stress as a result of salinomycin toxicity, the increased level of vitamins A and E in our work may be attributed to the occurrence of an equilibrium between the levels of vitamin uptake and their levels in the serum and body tissues, particularly the liver storage which probably has a role in enhancing the decreased serum level of these vitamins in salinomycin intoxicated sheep [29], also as vitamin A and E are fat-soluble, these increases might be due to lipid peroxidation in salinomycin toxicity. Although the status of antioxidant vitamins has not been clearly investigated in salinomycin toxicity in sheep, a number of previous studies demonstrated the decreased blood levels of such vitamins in the serum of the affected animals and suggest that this phenomenon was a consequence of elevation in the level of oxidative damages [14,30,31].…”
Section: Discussionmentioning
confidence: 86%
“…Accumulated data from many studies currently suggest that intracellular as well as extracellular oxidative stress may play an important role in inducing postischemic tissue injury (4)(5)(6)(7). At a very early phase of reperfusion, production of reactive oxygen species (ROS) associated with Rac1 has recently been reported to mediate intracellular oxidative stress (8), which consequently activates redox-dependent pathologic signals including NF-jB (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%